PERAWATAN MESIN TEMPEL PENANGKAP IKAN GUNA MENUNJANG KELANCARAN PENGOPERASIAN PERAHU NELAYAN DI KARIMUNJAWA - Ngatmin Ngatmin; Yulius Oscar; Gunawan Budi Santoso; Juwarlan Juwarlan; Prijo Harsono (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Community Service is an obligation for lecturers to carry out the Tridharma of Higher Education. The activity was carried out on June 18, 2022 in Jelamung RT 05 RW 02, Kemujan Karimujawa which was attended by 12 participants. The purpose of this service is to know how to maintain fishing boat outboard engines in general, which is used to change the engine oil, cleaning the air filter and fuel filter, testing the injectors and adjusting the valves, in addition it is to know the reason why the engine cannot start. Therefore, someone should check the fuel flow, opening the fuel filter and cleaning it. The implementation of this program is for fishermen’s beneficial, hance they can maintain and overcome engine damage for the sake of progress and increase the income.